Adaptation and validation of Child Oral Impact on Daily Performance index in 11- 14-year-old Chilean school children. - Constanza Vera; Ximena Moreno; Darling Rivera (Universidad de Concepción., 2013)
The health condition of a population is often rated through clinical indicators. However, the psychological and social impact of diseases on quality of life has been noticed of late. Objective: to adapt, in cultural terms, the Child- Oral Impact on Daily Performance (C-OIDP) questionnaire in its self- administered form and evaluate its psychometric properties among Chilean teenagers aged 11-14 from the city of Licantén, Chile, in 2013. Methodology: A cross-sectional study on scales validation. Face validity was determined by experts opinion, criterion validity by correlation with measures of self-rated health and dental treatment needs, internal consistency using the Cronbach's alpha, and temporal stability using the intraclass correlation coefficient (ICC) for test- retest within a 10-day window. The sample consisted of 203 students aged 11 to 14 years from the urban sector of Licantén city. Results: Five experts determined proper face validity of the C-OIDP scale. Regarding criterion validity, statistically significance association (p<0.05) were found, positive for treatment need and negative for oral health satisfaction. Internal consistency scale showed an alpha=0.719, all items showed correlations of 0.32 to 0.54 with the rest of the scale. The temporal stability gave an ICC=0.82. . Conclusion: the cultural adaptation of the self-administered C-OIDP questionnaire for Chilean students aged 11 to 14 years showed adequate psychometric properties, so it is a valid and reliable instrument to measure the oral health impact on quality of life in this population.